Poisson Equation and Discrete One-Sided Hilbert Transform for (C, α)-bounded Operators - Lizama-Yanez, C (Hebrew University Magnes Press, 2023)
We characterize the solutions of the Poisson equation and the domain of its associated one-sided Hilbert transform for (C, α)-bounded operators, α > 0. This extends known results for power bounded operators to the setting of Cesàro bounded operators of fractional order, thus generalizing the results substantially. In passing, we obtain a generalization of the mean ergodic theorem in our framework. Examples are given to illustrate the theory. © 2022, The Hebrew University of Jerusalem.